Cortical spreading depression preconditioning mediates neuroprotection against ischemic stroke by inducing AMP‐activated protein kinase‐dependent autophagy in a rat cerebral ischemic/reperfusion injury model. Issue 5 (12th January 2017) - Shen, Pingping; Hou, Shuai; Zhu, Mingqin; Zhao, Mingming; Ouyang, Yibing; Feng, Jiachun
Abstract: Cortical spreading depression (CSD), based on its similarities with peri‐infarct depolarization, is an ideal model for investigating transformation from the ischemic penumbra to infarct core. However, the underlying mechanisms remain unclear. To our knowledge, this is the first study to use a middle cerebral artery occlusion ischemic‐reperfusion (I/R) injury model to determine whether AMP‐activated protein kinase (AMPK)‐dependent autophagy contributes to the neuroprotection of CSD preconditioning in rat cortex. In this study, we topically applied a pledget soaked in 1 mol/L KCl solution on rat cortex for 2 h to elicite CSD or 1 mol/L NaCl solution as a control. The results demonstrated that CSD preconditioning significantly decreased the infarct volume, neurological deficits and neuronal apoptosis in the cortical penumbra of middle cerebral artery occlusion rats, which was inhibited by the autophagy inhibitor 3‐methyladenine (3‐MA, 200 nmol). Furthermore, CSD increased the protein levels of the autophagy markers LC3‐II, Beclin‐1 and the p‐AMPK (Thr 172 )/AMPK ratio at 12 h and decreased P62 and p‐P70S6K (Thr 389 ). Moreover, the AMPK inhibitor Compound C (20 mg/kg) down‐regulated the LC3‐II, p‐AMPK (Thr 172 )/AMPK and ULK1 levels, up‐regulated the P62 and p‐P70S6K (Thr 389 ) levels induced by CSD. The neuroprotection of CSD is likely a result of AMPK‐mediated autophagy activity and autophagy‐induced neuronal cells apoptosis inhibition. These novel findings support a central role for AMPK and autophagy in CSD‐induced ischemic tolerance. AMPK‐mediated autophagy may represent a new target for stroke. Abstract : Cortical spreading depression (CSD) is a novel model to investigate transformation from the ischemic penumbra to the infarct core, also called CSD preconditioning. We propose that SCD preconditioning could induce autophagy through AMPK‐mTOR signaling and decrease the infarct volume, ameliorate neurological deficits and neuronal apoptosis in the cortical penumbra of rats subject to middle cerebral artery occlusion, MCAO.